Design and Development of a Web-Based Sales Information System for Pempek Cek Ana Store - Dinda Despita Sari; Edi Supratman (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2026)
The sales process at Toko Pempek Cek Ana previously faced challenges in managing products, transactions, orders, and sales reports, highlighting the need for a computerized system to support sales activities. This study aims to design and develop a web-based sales information system for Toko Pempek Cek Ana. The Waterfall development method was applied through the stages of requirements analysis, system design, implementation, and testing. The system was developed to support customers, employees, and the owner in managing products, orders, payments, sales reports, and inventory monitoring. System testing using the Black Box Testing method showed that all tested functions operated according to the specified requirements. The results indicate that the developed system can facilitate sales activities and manage sales data in a more structured and efficient manner. Furthermore, the system can improve customer service and assist employees and the owner in managing and monitoring sales activities.